Evaluasi Sistem Informasi menggunakan COBIT 5 (Studi Kasus: Perusahaan Mentari Primajayaabadi) - Eka Waras Kristianto (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
PT Mentari Prima Jayaabadi is a manufacturing company that produces tapioca flour in large quantities. To support the company's operations, an information system is needed to support production. One of the systems to support is the implementation of an Enterprise Resource Planning (ERP) information system. Measurement and evaluation is necessary for the maturity level of the system, organization, management and all governance. This study aims to evaluate the performance of the ERP system using the COBIT Framework. The COBIT 5 framework is a framework for system and technology governance to get a better level of maturity and capability. It is hoped that this research will produce a method of system management and information technology at PT Mentari Primajayaabadi at level 3, namely Established Process, to level 4, namely Predictable. Where business processes can be measured and monitored to be good.